Community Perceptions Of "Ngantok Bheh Pepouw" Tradition And Its Role In Shaping Social Care Values: A Qualitative Study In Koto Bento - Mimi Mariani; Jalwis; Masnur Alam; Putra, Pristian Hadi (AJIS: Academic Journal of Islamic Studies, 2024)
Social concern, encompassing empathy, solidarity, and responsibility, is a fundamental value that sustains community life. In Indonesia, this value is expressed through participation in cooperation, or gotong royong, particularly in rural contexts. This study examines the tradition of Ngantok Bheh Pepouw in Koto Bento Village, Jambi Province, as a cultural practice that fosters social concern. This tradition involves community members collectively providing rice to bereaved families, symbolizing solidarity and easing their material and emotional burdens. Employing a qualitative approach, data were collected through observation, in-depth interviews, and documentation from key informants, including customary leaders, the village chief, and villagers. The findings indicate that Ngantok Bheh Pepouw strengthens communal bonds and integrates Islamic values of charity and compassion, serving as a form of moral and character education. The tradition demonstrates the interrelation of cultural, religious, and social dimensions in nurturing empathy, altruism, and civic responsibility. By sustaining and revitalizing such local wisdom, communities reinforce social cohesion, preserve cultural heritage, and cultivate inclusive, resilient societies capable of addressing contemporary social challenges.